2020
DOI: 10.1177/2050312120918999
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health and safety hazards faced by healthcare professionals in Taiwan: A systematic review of risk factors and control strategies

Abstract: Background: Healthcare professionals in Taiwan are exposed to a myriad of occupational health and safety hazards, including physical, biological, chemical, ergonomic, and psychosocial hazards. Healthcare professionals working in hospitals and healthcare facilities are more likely to be subjected to these hazards than their counterparts working in other areas. Objectives: This review aims to assess current research literature regarding this situation with a view to informing policy makers and practitioners abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…A possible factor and mechanism for the higher rate of prostate and breast cancer in male and female pharmacists is work-related exposure to carcinogens and the practice of pharmacy itself, which includes long-working hours and working on the feet. The present study showed that the workplace is an important factor that exposes employees to several important occupational cancers, an insight that is also supported in the literature [ 3 ]. The study showed that pharmacists are constantly exposed to a complex variety of occupational risks in the course of their work, an observation also made in the literature [ 1 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A possible factor and mechanism for the higher rate of prostate and breast cancer in male and female pharmacists is work-related exposure to carcinogens and the practice of pharmacy itself, which includes long-working hours and working on the feet. The present study showed that the workplace is an important factor that exposes employees to several important occupational cancers, an insight that is also supported in the literature [ 3 ]. The study showed that pharmacists are constantly exposed to a complex variety of occupational risks in the course of their work, an observation also made in the literature [ 1 ].…”
Section: Discussionsupporting
confidence: 86%
“…Occupational risks in clinical and non-clinical practitioners can vary depending on their specific profession, the nature of their work and their workplace type and environment [ 2 ]. As highlighted by Che Huei et al [ 3 ] and Lombardo and Roussel [ 4 ], employees in hospital settings are exposed to physical hazards such as radiation; psychological hazards such as shift work; biological hazards such as bacterial or viral infections; and chemical hazards such as antineoplastic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…24–26 These occupational ergonomic hazards at hospitals include the design of the workplace and workstation, working in awkward positions, and repetitive procedures. 9 , 27 Program administrators should consider a job’s characteristics and required physical tasks to provide important intervention opportunities for preventing work-related MSDs among the staff. A behavioral preventive model should be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare work settings are more complex and healthcare workers, apart from other job-related issues that are common across organizations, are prone to health-related issues [ 18 ]. Hospitals’ environments contain health hazards including ergonomic, chemical, biological, and physical hazards that add to work-related difficulties [ 22 ]. Employees, as such, expect job safety, coworker safety, supervisor safety, management safety practices, and safety programs to be in place in their work environment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%